SYNTHESIS AND CHARACTERIZATION OF BENZOTRIAZOLIUM-BASED IONIC LIQUIDS FOR TECHNETIUM-99M SEPARATION FROM MOLYBDENUM BY IL-MEDIATED EXTRACTION PROCESS - Yanuar Setiadi; Muhamad Basit Febrian; Ahmad Mudzakir; Azmairit Aziz; Duyeh Setiawan; Anna Kurnia Illahi; Dwi Ayu Rahmawati (BATAN, 2019)
Various separation techniques for separation of technetium-99m (99mTc) from molybdenum-99 (99Mo) are being developed to overcome the drawbacks of using 99Mo from neutron activation technique. Ionic liquids (ILs) were used in many extraction processes in metal separation due to their high selectivity. In this research, two benzotriazolium-based ionic liquids were used as co-extractant in 99mTc/ Mo separation process via liquid-liquid extraction. 1-octyl-3-methyl-benzotriazolium iodide ([MeOcBtu]I) and 1-octyl-3-methyl-benzotriazolium bis (trifluoromethanesulfonyl) imide ([MeOcBtu]TF2N) were successfully synthesized and analyzed by FTIR, 1H-NMR and 13C-NMR. Extraction processes were conducted in various organic solvents, pH, and extraction time without/ with ionic liquids addition. The data of ratio between 99mTc distribution coefficient compared to Mo distribution coefficient showed that the addition of ionic liquids exhibited significant improvement of separation factor. The separation factor of extraction using conventional water immiscible solvent ranged between 0 – 8 and increased to 30 – 600 as ILs were added. The optimum conditions which achieved highest separation factor were pH 14 using [MeOcBtu]I-chloroform. Benzotriazolium-based ionic liquid potential to be developed as extractant in the separation of 99mTc from 99Mo. Keywords: Ionic liquids, benzotriazolium, technetium-99m, molybdenum, liquid-liquid extraction.